The Influence of Achievement Motivation and Self-Regulated Learning (SRL) on Students’ Mathematics Learning Outcomes - Anwaril Hamidy; Pika Merliza (Institut Agama Islam Negeri (IAIN) Samarinda, 2019)
This study explores the significance of influence of achievement motivation and SRL toward students’ mathematics learning outcomes. This was an ex post facto research. The population was all tenth-grade students of MAN 2 Samarinda, West Kalimantan, Indonesia in the school year 2013/2014. The sample was selected by cluster sampling, as well as obtained four classes as a sample. The data were collected by questionnaires of achievement motivation and SRL, and math formative test. Furthermore, the data were analyzed by using multiple regression analysis. The results of this study is the assumption of regression equation Ŷ = -21,682 + 0,400X1 + 0,239X2 with F value is 40,043 and the significance is 0,000. Hence, there is a significant combination of achievement motivation and SRL through students’ mathematics achievement.